2013
DOI: 10.1371/journal.pone.0061140
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Vulnerable Atherosclerotic Plaque and Prediction of Thrombosis Events in a Rabbit Model Using 18F-FDG -PET/CT

Abstract: BackgroundDetection of vulnerable plaques could be clinically significant in the prevention of cardiovascular events. We aimed to compare Fluorine-18 fluorodeoxyglucose (18F-FDG) uptake in vulnerable and stable plaques, and investigate the feasibility of predicting thrombosis events using Positron Emission Tomography/Computed Tomography (PET/CT) angiography.MethodsAtherosclerosis was induced in 23 male New Zealand white rabbits. The rabbits underwent pharmacological triggering to induce thrombosis. A pre-trigg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 17 publications
2
39
1
Order By: Relevance
“…This model consists of placing a vascular (arterial) injury in rabbits receiving a hyperlipidaemic diet [5254]. Of all preclinical models representative of the clinical situation, porcine models may be the best option for the investigation of atherosclerosis.…”
Section: F-fdg Pet In Preclinical Studiesmentioning
confidence: 99%
“…This model consists of placing a vascular (arterial) injury in rabbits receiving a hyperlipidaemic diet [5254]. Of all preclinical models representative of the clinical situation, porcine models may be the best option for the investigation of atherosclerosis.…”
Section: F-fdg Pet In Preclinical Studiesmentioning
confidence: 99%
“…Zhao et al investigated detection of thromboembolic event in an atherosclerotic rabbit model, induced by balloon injury within the abdominal aorta 24 . After additional deendothelialization of the aorta and pharmacological triggering PET/CT was conducted for the detection of thrombus formation 24 . After gross anatomical analysis and histopathological evaluation similar to our study, 15 of 23 thrombi were correctly diagnosed.…”
Section: Detection Of Thrombus Formation Is Still Important In Micro-mentioning
confidence: 99%
“…After gross anatomical analysis and histopathological evaluation similar to our study, 15 of 23 thrombi were correctly diagnosed. After adaption of the 18 F-FDG uptake based on the morphological findings a maximal sensitivity of 75.4% and specificity of 88.5% with a positive and negative predictive value of 53.5% and 98.5% was achieved 24 . In contrast to this method ICG videoangiography has no radiation and is easily performed in the intraoperative setting, since its function is based on simple fluorescence angiography.…”
Section: Detection Of Thrombus Formation Is Still Important In Micro-mentioning
confidence: 99%
“…Overall, it has been shown that 18 F-FDG with PET/CT can be used to assess atherosclerotic plaques of varying compositions and throughout the different stages of the disease. 63 18 F-FDG has shown to be functional for understanding the underlying pathology involved in atherosclerosis.…”
Section: Preclinical Evaluation Of 18 F-fdg-pet/ctmentioning
confidence: 99%